2013
DOI: 10.1186/1479-5868-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Is walking to school associated with improved metabolic health?

Abstract: BackgroundActive commuting to/from school is an important source of physical activity that has been declining over the past years. Although it is an affordable and simple way of increasing physical activity levels it is still unclear whether it has enough potential to improve health. Therefore, the aim of this cross sectional study was to examine the relationship between active commuting to/from school and metabolic risk factors in 10 to 12 year old children.MethodsParticipants were 229 adolescents, selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 31 publications
(41 reference statements)
2
46
1
2
Order By: Relevance
“…[42][43][44] NHANES data 42 suggest U.S. students would accumulate an extra 4.5 minutes of moderate-to-vigorous physical activity each day if they spent 30 minutes per day actively commuting to and from school. Since 1969, the proportion of elementary and middle school students walking or biking to school fell 35 percentage points, from 47.7% to 12.7%.…”
Section: Active Transportationmentioning
confidence: 99%
“…[42][43][44] NHANES data 42 suggest U.S. students would accumulate an extra 4.5 minutes of moderate-to-vigorous physical activity each day if they spent 30 minutes per day actively commuting to and from school. Since 1969, the proportion of elementary and middle school students walking or biking to school fell 35 percentage points, from 47.7% to 12.7%.…”
Section: Active Transportationmentioning
confidence: 99%
“…[1][2] In view of the important role played by physical activity (PA) in overall health promotion, and the decline in PA among children and adolescents, [3][4][5][6][7] it becomes crucial for each society to review opportunities available to promote increased PA among their children and youth.…”
mentioning
confidence: 99%
“…11 It was also possible to identify walking as the main pattern of transportation to school while cycling was found to be unusual in Portuguese children. 12 Additionally, in countryside regions it was found that around 30% of children (n = 3000) aged 7-to 8-years-old commuted either by foot or by cycling on a regular basis during school days 13 ). Distance emerged as a significant predictor of active commuting to school as increased distances were associated with higher levels of passive transportation to school.…”
Section: Active Play and Leisure: Dmentioning
confidence: 99%